Association of n-3 polyunsaturated fatty acid intakes with juvenile myopia: A cross-sectional study based on the NHANES database - Zhou, Zixiu; Li, Sizhen; Yang, Qingsong; Yang, Xiaodong; Liu, Yating; Hao, Kuanxiao; Xu, Shanshan; Zhao, Na; Zheng, Pengjie (Frontiers in Pediatrics, 2023)
Aim: Evidence suggests that inflammation is involved in the development of myopia. n-3 polyunsaturated fatty acids (n-3 PUFAs) have vascular dilatation, anti-inflammatory and other effects, and may be involved in the myopia control. Herein, it is of great implications to explore the relationship between n-3 PUFAs and juvenile myopia to control and alleviate of myopia among teenagers by dietary intervention. Methods: Sociodemographic data, nutrient intake, cotinine, PUFAs and the refractive status of the eye of 1,128 juveniles were extracted from the National Health and Nutrition Examination Survey (NHANES) database in this cross-sectional study. The potential covariables were age, gender, total polyunsaturated fatty acids (TPFA) and cotinine. TPFA, alpha-linolenic acid (ALA), octadecatetraenoic acid (SDA), eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), docosahexaenoic acid (DHA) and their calculated value based on energy density were the study variables. The association between n-3 PUFAs and juvenile myopia were evaluated using univariate and multivariate logistic regression analyses, with odds ratio (OR) and 95% confidence intervals (CIs). Results: Among the participants, 788 (70.68%) were normal vision, 299 (25.80%) were low myopia and 41 (3.52%) were high myopia. The mean EPA and DHA levels in the normal vision, low myopia and high myopia group were 0.09 (0.01), 0.11 (0.02), and 0.06 (0.02) gm and 0.16 (0.01), 0.12 (0.03) and 0.20 (0.03) gm, respectively. The mean energy density of EPA and DHA were significant differences among the three groups (P=0.006 and P=0.002). Compared with normal vision group, higher intake of EPA was associated with the high myopia [OR=0.39, 95% CI: (0.18-0.85)] after adjusting covariables including age, gender, TPFA and cotinine. However, there was no significant relationship between FAs levels and low myopia. Conclusion: Higher intake of n-3 PUFA was related to the low myopia among juvenile, which may provide dietary strategies for myopia prevention. In addition, further prospective study needs to be conduct to explore the influence of n-3 PUFA in reducing the risk of juvenile myopia.